2018
DOI: 10.4103/aer.aer_190_17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of targeted preoperative optimization on clinical outcome in emergency abdominal surgeries: A prospective randomized trial

Abstract: Background:Perforation peritonitis continues to be one of the most common surgical emergencies that need a surgical intervention most of the times. Anesthesiologists are invariably involved in managing such cases efficiently in perioperative period.Aims:The assessment and evaluation of Acute Physiology and Chronic Health Evaluation II (APACHE II) score at presentation and 24 h after goal-directed optimization, administration of empirical broad-spectrum antibiotics, and definitive source control postoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Preoperative goal-directed fluid therapy was used in two of the multimodal cohort studies which showed significant reduction in mortality [ 3 , 29 ]. Another small study used a goal-directed fluid optimization protocol in the preoperative holding room in patients with perforated peptic ulcer and showed reduced length of stay and mortality compared with a usual management control group [ 47 ]. Lactate guided resuscitation of patients with septic shock has been shown to reduce mortality [ 46 ] and may be beneficial in patients undergoing emergency laparotomy.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative goal-directed fluid therapy was used in two of the multimodal cohort studies which showed significant reduction in mortality [ 3 , 29 ]. Another small study used a goal-directed fluid optimization protocol in the preoperative holding room in patients with perforated peptic ulcer and showed reduced length of stay and mortality compared with a usual management control group [ 47 ]. Lactate guided resuscitation of patients with septic shock has been shown to reduce mortality [ 46 ] and may be beneficial in patients undergoing emergency laparotomy.…”
Section: Resultsmentioning
confidence: 99%
“…Full preoperative counselling, which is known to reduce post-operative stress, pain and anxiety [24], may not be possible in emergency setting; nevertheless, information such as details of procedure, possible perioperative complications, need for creation of stoma and length of hospitalisation can be communicated with patients and their family before the procedure. On the other hand, although complete optimisation of medical conditions cannot be achieved in emergency setting, objective intravenous fluid and antibiotic resuscitation in emergency major abdominal surgery are crucial and feasible [25]. Apart from these, the rest of intraoperative and post-operative components of ERAS protocols [26][27][28][29][30][31] are achievable in emergency settings.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of preoperative optimization on clinical outcome following emergency laparotomy has recently been studied in a prospective randomized trial of 94 patients with generalized peritonitis due to gastrointestinal perforation[19]. This study demonstrated a shorter length of hospital stay and a lower rate of postoperative death in patients receiving standardized, algorithmic management in the preoperative holding room – where central venous cannulation was performed and goal-directed optimization was done.…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%